2018
DOI: 10.1038/s41598-018-27222-6
|View full text |Cite|
|
Sign up to set email alerts
|

Triple-negative invasive breast carcinoma: the association between the sonographic appearances with clinicopathological feature

Abstract: In this study, we aimed to evaluate the clinical and pathological factors that associated with sonographic appearances of triple-negative (TN) invasive breast carcinoma. With the ethical approval, 560 patients who were pathologically confirmed as invasive breast carcinoma were reviewed for ultrasound, clinical, and pathological data. Logistic regression analysis was used to identify the typical sonographic features for TN invasive breast carcinomas. The effect of clinical and pathological factors on the sonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 36 publications
5
47
3
Order By: Relevance
“…In these studies, histologic grade did not differ between LAR-TNBC and control group, whereas we observed a lower percentage of poorly differentiated tumors in our group of LAR-TNBC. Lower histological grading and slower growth can be associated with a more spiculated, infiltrating growth pattern, giving the surrounding tissue time for stromal interactions (7). This may explain our mammographic findings; however, they seem to be contradictory to the more frequent lobular sonographic patterns of LAR in our study.…”
Section: Figure 2 Ultrasound Images Of Bl-tnbc With Lobulated Margincontrasting
confidence: 68%
See 2 more Smart Citations
“…In these studies, histologic grade did not differ between LAR-TNBC and control group, whereas we observed a lower percentage of poorly differentiated tumors in our group of LAR-TNBC. Lower histological grading and slower growth can be associated with a more spiculated, infiltrating growth pattern, giving the surrounding tissue time for stromal interactions (7). This may explain our mammographic findings; however, they seem to be contradictory to the more frequent lobular sonographic patterns of LAR in our study.…”
Section: Figure 2 Ultrasound Images Of Bl-tnbc With Lobulated Margincontrasting
confidence: 68%
“…Several features of mammographic and sonographic breast findings are evaluated algorithmically to minimize radiologist-dependent subjective ratings. TNBC is known to present more often benign characteristics in clinical imaging such as lobulated, oval-shaped, and circumscribed margins, than other types of BC (7). Benign classification and misinterpretation can lead to diagnostic delay and negative impact on the outcomes of BC (8).…”
Section: Conclusion: the Histopathological Subtype Of Tnbc Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 620 patients with TNBC, with ages ranging from 28 to 95 years, were included in the analysis. Of the included studies, 8 studies focused on the evaluation of the tumor shape of TNBC, all of which showed that the occurrence rate of a “round/oval shape” in TNBC was higher than that in non‐TNBC. Of the included studies, there were 7 studies evaluating the tumor margin of TNBC.…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesized that those lesions mimicked the morphology of benign lesions because of their rapid cellular proliferation. [30][31][32] One of the most interesting findings of our study was the association between sonographic orientation and molecular subtypes in predicting BC outcomes. This may be explained by diverse imaging patterns among different molecular subtypes of BC.…”
Section: Discussionmentioning
confidence: 71%